The Effect of Digital Marketing, Electronic Word of Mouth, and Lifestyle on Purchasing Decisions (Study on Vegetable Product MSMEs in Kediri Regency) - Harwida, Gleydis; Sudarmiatin; Wardana, Ludi Wishnu (Formosa Journal of Applied Sciences, 2024)
This study investigates the influence of digital marketing, eWOM, and lifestyle on purchasing decisions for vegetable products in Kediri Regency.  To measure the influence of digital marketing, eWOM, and lifestyle on purchasing decisions, this research uses a quantitative descriptive approach. It involved a population of MSME consumers of Vegetable Products in Kediri District, with 120 respondents chosen at random. Data is collected using a questionnaire and analyzed using validity, reliability, classical assumption tests, and multiple regression analysis. It took one month to finish this study, which began in August of 2024. The results of the analysis show that Digital Marketing, Electronic Word of Mouth, and Lifestyle significantly influence Purchasing Decisions in MSMEs of vegetable products in Kediri District, with Digital Marketing and eWOM contributing positively.